Implementation of Planning and Budgeting as a Business Development Strategy: A Case Study of Pataya 'Thai Tea' Shop - Nur abdi, Muhammad; Syah, Firman; Muhammad Iqram (Cita konsultindo, 2025)
This study aims to provide an understanding of the implementation of planning and budgeting in the context of developing the Pataya